DISSEMINATION OF FERTILIZER PACKAGING LITERATURE AND SOIL CONSERVATION ON FARMING GROUP IN SUNGAI AUR DISTRICT PASAMAN BARAT - J Jamilah; S Syahrial; Yulia Rahmawati Z; Milda Ernita; Z Zahanis; Yopa Dwi Mutia (Lembaga Penelitian dan Pengabdian Pada Masyarakat Universitas Tamansiswa Padang, 2022)
Fertilization is important for plants. Appropriate and efficient fertilizer application will result in optimal plant growth and production. Farmers need to know and understand the artificial fertilizers that are sold at fertilizer kiosks, by reading the fertilizer brand including the ingredients and the many ingredients. The aim was to introduce the community, especially the Mekar Abadi and Mekar Jaya farmer groups, in Jorong Muara Tapus, Kenagarian Sungai Aur, to understanding the importance of understanding literacy in fertilizer packaging and soil conservation so that they can use artificial fertilizers effectively and efficiently. Service activities for the Mekar Abadi and Mekar Jaya Farmer Groups have been carried out in June 2022, the activities include; providing information to the Department of Agriculture, Food Security, and Livestock; Sungai Aur District; Wali Nagari Sungai Aur, Wali Jorong Muara Tapus and PPL in Sungai Aur will carry out outreach activities. Next, formulate a model of service activities that will be carried out by the Team together with the community of farmer groups in the Aur river. Counseling was carried out at night, remembering that more audiences are present and everyone can take the time to participate in these activities. The activity technique before the lecture was to distribute questionnaires to determine the understanding of farmers' literacy on the fertilizer brand on the fertilizer packaging, next was a lecture and question and answer discussion about the audience's understanding of the material given. In general, farmers in Jorong Muara Tapus Kenagarian Sungai Aur, Sungai Aur District, are not only maize farmers but also most oil palm farmers. The ability of farmers to distinguish between genuine and fake fertilizers, as well as to distinguish between fertilizers containing macro and micronutrients is still very low. Farmers still do not understand efforts to preserve soil fertility through soil conservation measures. Conservation techniques are also important to maintain soil fertility so that fertilization is more effective and efficient.